Additional cytogenetic abnormalities and variant t(9;22) at the diagnosis of childhood chronic myeloid leukemia: The experience of the International Registry for Chronic Myeloid Leukemia in Children and Adolescents - Millot, Frédéric; Dupraz, Christelle; Guilhot, Joelle; Suttorp, Meinolf; Brizard, Françoise; Leblanc, Thierry; Güneş, Adalet Meral; Sedlacek, Petr; De Bont, Evelyne; Li, Chi Kong; Kalwak, Krzysztof; Lausen, Birgitte; et al. (Cancer, 2017)
BACKGROUND: In the adult population with newly diagnosed chronic myeloid leukemia (CML), variant translocations are usually not considered to be impairing the prognosis, whereas some additional cytogenetic abnormalities (ACAs) are associated with a negative impact on survival. Because of the rarity of CML in the pediatric population, such abnormalities have not been investigated in a large group of children with CML. METHODS: The prognostic relevance of variant t(9;22) and ACAs at diagnosis was assessed in 301 children with CML in the chronic phase who were enrolled in the International Registry for Chronic Myeloid Leukemia in Children and Adolescents. RESULTS: Overall, 19 children (6.3%) presented with additional cytogenetic findings at diagnosis: 5 children (1.7%) had a variant t(9;22) translocation, 13 children (4.3%) had ACAs, and 1 had both. At 3 years, for children with a classic translocation, children with ACAs, and children with a variant t(9;22) translocation who were treated with imatinib as frontline therapy, the probability of progression-free survival (PFS) was 95% (95% confidence interval [CI], 91%-97%), 100%, and 75% (95% CI, 13%-96%), respectively, and the probability of overall survival (OS) was 98% (95% CI, 95%-100%), 100% (95% CI, 43%-98%), and 75% (95% CI, 13%-96%), respectively. No statistical difference was observed between the patients with classic cytogenetic findings and those with additional chromosomal abnormalities in terms of PFS and OS. CONCLUSIONS: In contrast to adults with CML, additional chromosomal abnormalities observed at diagnosis do not seem to have a significant prognostic impact. Cancer 2017;123:3609-16. © 2017 American Cancer Society.
Keywords: Real-Time Polymerase Chain Reaction; child; následné studie; Chromosome Aberrations; lidé; výsledek terapie; Chromosomes, Human, Pair 9; registrace; Chromosomes, Human, Pair 22; lidské chromozomy, pár 9; Survival Analysis; neparametrická statistika; chronic myeloid leukemia; rozvrh dávkování léků; Internationality; analýza přežití; vztah mezi dávkou a účinkem léčiva; retrospektivní studie; internacionalita; Humans; protokoly protinádorové kombinované chemoterapie; Follow-Up Studies; Dose-Response Relationship, Drug; Philadelphia-positive; chronická myeloidní leukemie; Registries; cytogenetic; přežití bez známek nemoci; genetická predispozice k nemoci; Statistics, Nonparametric; Drug Administration Schedule; Disease-Free Survival; Kaplanův-Meierův odhad; chromozomální aberace; Kaplan-Meier Estimate; Treatment Outcome; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; kvantitativní polymerázová řetězová reakce; Retrospective Studies; Genetic Predisposition to Disease; Antineoplastic Combined Chemotherapy Protocols; imatinib; lidské chromozomy, pár 22